Identifying key challenges in the integration of migrant women into local communities expert survey: a monitoring study - Б. Сагындыкова; Ф. Максуд (Хабаршы. Психология және социология сериясы)
The article presents the findings of an expert survey conducted to identify the key challenges faced by migrant women during their integration into the local communities in a monitoring mode. The survey, carried out between August and November 2023, was supported by the International Labor Organization (ILO) under The UN, the Ministry of Foreign Affairs of the Kingdom of Norway, and the NGO "Sana Sezim". Migrant women represent one of the most vulnerable demographic group, as they migrate alone or with children, in addition to migrating with their families. The monitoring survey targeted main objectives, which was conducted in two main areas that cause the main challenges for migrant women during their adaptation to the local communities: сhildren's access to schools; migrant women access to free medical services, including health monitoring, pregnancy registration.